Description of a new genus and two new species of freshwater crabs (Decapoda: Brachyura: Potamonautidae) from southeastern Madagascar. Issue 3 (11th August 2021) - Cumberlidge, Neil; Soma, Julia B; Leever, Ellen M; Clark, Paul F; Daniels, Savel R
Abstract: A new genus of freshwater crab, Crosnautes n. gen., and two species, C. ranomafana n. sp. and C. alainus n. sp., are described from forested highlands in southeastern Madagascar. The new genus can be distinguished on phylogenetic and morphological grounds. Crosnautes n. gen. has a suite of morphological characters that differentiate it from all other Malagasy genera: a carapace with a faint and interrupted postfrontal crest, short ambulatory legs, a mandibular palp with a conspicuous anterior lobe, a long third maxilliped exopod that extends across the width of the merus, and eyestalks and corneas of normal length and size. The two new species can be differentiated from each other by the size of the distal tooth on the cheliped carpus, the width of the first gonopod, and the length of the ambulatory legs. The new species are endemic to Madagascar and are compared to, and distinguished from, Foza raimundi Reed & Cumberlidge, 2006, the sister taxon to the new genus, as well as to all of the other Madagascan genera of freshwater crabs.